Root Canal Treatment of Mandibular Second Premolar with Three Separate Roots and Canals Using Spiral Computed Tomographic - V. P. Hariharavel; A. Ashok Kumar; C. Ganesh; Sankar Annamalai; Kavitha Ramar; R. Aravindhan (Case Reports in Dentistry)
Anatomic and internal morphology of a root canal system is more complex and differs for each individual tooth of which mandibular premolars have earned the reputation for having aberrant anatomy. The occurrence of three canals with three separate foramina in mandibular second premolars is very rare. A wider knowledge on both clinical and radiological anatomy especially spiral computed tomographic is absolutely essential for the success of endodontic treatment. These teeth may require skillful and special root canal special shaping and obturating techniques. This paper reports an unusual case of a mandibular second premolar with atypical canal pattern that was successfully treated endodontically.